The Effect of Expressive Writing on Psychological Distress in Patients with Vitiligo: A Randomized Clinical Trial - Leili Borimnejad; Alireza firooz; Hosein Mortazavi; Nessa Aghazadeh; Zahra Halaji (Iran University of Medical Sciences, 2015)
Objective: In this clinical trial, we examined whether or not expressive writing as a psychological intervention reduces psychological distress in vitiligo patients receiving phototherapy.  Method: A total of 139 adult vitiligo patients were asked to complete the GHQ-28 in order to identify their psychiatric disturbances. The GHQ-28 scores showed that 78 patients (56.5%) had psychiatric distress. They were later enrolled in this randomized controlled trial conducted during June 2009 until Dec 2009 at Razi Hospital in Tehran. Patients were randomly divided into 2 groups. Group A underwent the routine treatment protocol. Group B did the same, but they were also instructed to practice 'expressive writing'. The intervention continued 4 weeks. After 4 weeks, patients in both groups were re-evaluated using the GHQ-28.  Results: The overall GHQ-28 scores and sub-scores were significantly reduced in both groups A (47.9+/-11.71, P = 0.000) and B (48.94+/-10.69, P = 0.000) after 4 weeks of intervention. However, no statistically significance difference was found between the two groups in terms of their overall scores (P = 0.7) and their sub-scores.  Conclusion: The effect of expressive writing on reducing psychological distress in patients with vitiligo remains equivocal. Nonetheless, further studies with larger sample sizes and of longer duration especially in non-western cultural contexts are recommended.